PENGARUH PEMUPUKAN PADA TANAMAN JARAK PAGAR ( JATHROPA CURCAS L. ) TERHADAP DAYA SERAP LOGAM BERAT KROMIUM - Sudaryono, Sudaryono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
Productivity of agricultural land contaminated with tannery wastes originatedchromium is decreased. Crop produced on the contaminated land is toxic for human and animal. An alternative to solve this problem is by using plants which are able to tolerate the contaminant, produce high yield, able to accumulate highconcentration of the contaminant and non consumed. The aim of this research was to find out the effect of cattle manure and biofertilizer in supporting the giant castor bean grown on tannery wastes originated-chromium contaminated land and the ability of cattle manure and biofertilizer in influencing chromium absorptionby the plant.The result showed that giant castor bean can grow normally on chromium contaminated soil. There was no interaction between cow manure and biofertilizer for all observed variables. Cattle manure and biofertilizer have no effect to almost all of the observed variables, except that cattle manure affecting total leaf number and leaf area ratio. Giant castor bean grown on contaminated soils contain 5 – 9 ppm chromium in the leaf. Therefore, giant castor bean could not be considered as higher accumulator plant.